Getting to know Benign Prostatic Hyperplasia (BPH) in daily practice - Ikhwan, Haznur (Science Midwifery, 2024)
BPH or Benign Prostatic Hyperplasia is a histological diagnosis due to hyperplasia of stromal cells and epithelial cells of the prostate gland. Thought to occur due to the influence of hormones, dietary patterns, microtrauma, inflammation, obesity, and physical activity Occurs in elderly males and has testicles that still produce testosterone. This paper was created by searching the literature from clinical practice guides, scientific literature, websites, and textbooks on the topic of BPH. Results and Discussion: BPH often occurs in old age, has to do with diet, comorbidities, physical activity/exercise, smoking, work and education. Some treatments, namely conservative therapy, medicamentosa, phytopharmaceuticals and surgery. The selection of therapy starts from the least invasive aimed at improving quality of life. BPH is difficult to prevent, preventive measures are very important for prevention. Conclusion: BPH can decrease quality of life although not deadly. Management depends on the level of the patient's complaint, complications, available facilities, and the patient's choice. The ability to recognize diseases, diagnose and provide therapy is not the same because of differences in facilities and human resources. It is hoped that doctors in remote areas can recognize and diagnose BPH early in order to handle patients as well as possible.